Real‐life data on Selexipag for the treatment of pulmonary hypertension. (1st February 2019) - Barnikel, Michaela; Kneidinger, Nikolaus; Klenner, Friederike; Waelde, Andrea; Arnold, Paola; Sonneck, Torben; Behr, Jürgen; Neurohr, Claus; Milger, Katrin
Abstract : Selexipag is an orally available selective IP prostacyclin‐receptor agonist licensed since 2016 for the therapy of pulmonary arterial hypertension (PAH). We aimed to describe real‐life data of patients with pulmonary hypertension (PH) treated with selexipag. We analyzed all patients initiated with selexipag from July 2016 to April 2018 at the Department of Internal Medicine V, University of Munich. Non‐invasive and invasive parameters corresponding to the risk assessment were collected at baseline and follow‐up (FU). Furthermore, we recorded tolerability. Twenty‐six patients were treated with selexipag, of whom 23 had PAH and three had chronic thromboembolic PH. At baseline, most patients were in function class (FC) II or III (42% and 54%, respectively). All patients were under medical treatment for PH, mostly dual therapy (92%). One or more side effects were noted in 19 patients, while seven reported no side‐effects. FU assessment was available in 20 patients after 149 ± 80 days of treatment. Nt‐proBNP (median, baseline 1641 pg/mL, FU 1185 pg/mL, P  = 0.05) and PVR (mean ± SD, baseline 8.5 ± 4.3 WU, FU 5.6 ± 1.1 WU; P  < 0.05) improved significantly. At FU, at least one risk assessment parameter improved in nine patients (45%), all parameters remained in the same risk group in seven patients (35%), and at least one parameter deteriorated in four patients (20%). Interestingly, patients with any side effect throughout the dose titration had a better treatment response than those without any side effects. In our real‐life cohort, the majority of patients with PH treated with selexipag showed a stable or improved risk assessment at FU.